2019
DOI: 10.1016/j.chb.2019.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Mobile game-based learning in secondary education: Students’ immersion, game activities, team performance and learning outcomes

Abstract: Studies on game-based learning show positive effects, but insights into the relationship between students' game activities and the outcomes of these activities are lacking. In this study of the game "NoCredit, GameOver! ®" (NCGO), students' game activities are explored and related to their learning outcomes and performance in the game. Secondary school students used tablets to access virtual information about having debts and to perform tasks in an urban environment. Data were gathered from 181 students who co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 23 publications
7
54
0
10
Order By: Relevance
“…Thus, the cooperative learning approach can improve learning effects. This result was similar to related research [12,16,20], which indicated students of low achievement increase their motivation and learning confidence.…”
Section: Learning Effects Of Using Cooperative Learningsupporting
confidence: 91%
See 3 more Smart Citations
“…Thus, the cooperative learning approach can improve learning effects. This result was similar to related research [12,16,20], which indicated students of low achievement increase their motivation and learning confidence.…”
Section: Learning Effects Of Using Cooperative Learningsupporting
confidence: 91%
“…Previous research found that mobile learning is not intended to be a complex learning process but should facilitate the learning process of students. Appropriate application development combined with mobile devices can enhance educational outcomes [12,16,20]. These results are consistent with previous studies, which indicated that mobile learning can be applied to improve students' satisfaction [34,35] and technology acceptance [35].…”
Section: The Learning Satisfaction Interest and Technology Acceptansupporting
confidence: 90%
See 2 more Smart Citations
“…Learning with digital content significantly represents gamebased learning today. Huizenga, Admiraal, Ten Dam, and Voogt (2019) stated that teachers can continue their teaching outside the classroom thanks to mobile-based games. They stated that student behavior is important in the game process and that the desire to win the game may have negative results in terms of learning.…”
Section: Introductionmentioning
confidence: 99%